2020
DOI: 10.1186/s12967-020-02372-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood transcriptomic investigation identifies long non-coding RNAs as regulators in sepsis

Abstract: Background: Sepsis is a fatal disease referring to the presence of a known or strongly suspected infection coupled with systemic and uncontrolled immune activation causing multiple organ failure. However, current knowledge of the role of lncRNAs in sepsis is still extremely limited. Methods: We performed an in silico investigation of the gene coexpression pattern for the patients response to all-cause sepsis in consecutive intensive care unit (ICU) admissions. Sepsis coexpression gene modules were identified u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…WGCNA has also been used to analyze correlation patterns in sepsis. These research efforts focused on inflammatory cells in vitro ( 21 ), long non-coding RNA ( 22 ), transcription factors and miRNA ( 23 ) based on samples with or without sepsis, but did not distinguish between patients with positive outcomes from those with negative outcomes. A recent study identified two transcription factors, CEBPB and ETV6, associated with mortality outcome via WGCNA ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA has also been used to analyze correlation patterns in sepsis. These research efforts focused on inflammatory cells in vitro ( 21 ), long non-coding RNA ( 22 ), transcription factors and miRNA ( 23 ) based on samples with or without sepsis, but did not distinguish between patients with positive outcomes from those with negative outcomes. A recent study identified two transcription factors, CEBPB and ETV6, associated with mortality outcome via WGCNA ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the genome-wide expression profiling of sepsis [13,16,17]. The differential gene expression has been well characterized between sepsis versus non-sepsis inflammatory responses [18], survivors versus non-survivors [19,20], and sepsis of viral versus bacterial causes [21]. Two endotypes of sepsis were identified [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, MALAT1 was not co-expressed with numerous DEGs but analysis of hybridisation energy showed that it can regulate even 85 of them. It suggests that MALAT1 can act at various molecular level not only transcript blocking [41]. Thus, our observa-tion and previous literature reports persuade us to continue researching MALAT1 in the obesity regulation context because the interactions are still not clear.…”
Section: Validation Of Rna-seq Resultsmentioning
confidence: 59%